A Model of Perinatal Ischemic Stroke in the Rat: 20 Years Already and What Lessons? - Charriaut-Marlangue, Christiane; Baud, Olivier (Frontiers in Neurology, 2018)
Neonatal hypoxia–ischemia (HI) is a common cause of neonatal brain injury and results in cerebral palsy, learning disabilities, and epilepsy. In addition to global cerebral ischemia arising from systemic asphyxia, recent data suggest a higher incidence of focal ischemia–reperfusion leading to stroke in near-term neonates. Pre-clinical studies in the field of cerebral palsy research used, and still today, the classical HI model in the P7 rat originally described by Rice and Vannucci in 1981. At the end of the 90s, we designed a new model in the P7 rat to investigate the acute and long-term pathophysiology of neonatal arterial ischemic stroke, particularly the phenomenon of reperfusion injury and its sequelae (reported in 1998). Cerebral blood-flow and cell death/damage correlates have been fully characterized. Pharmacologic manipulations have been applied to the model to test therapeutic targets. The model has proven useful for the study of seizure occurrence, a clinical hallmark for neonatal ischemia in babies. Main pre-clinical findings obtained within these 20 last years are discussed associated to clinical pattern of neonatal brain damage.